Prevalence of insulin resistance in obese adolescents - Aman B. Pulungan; Ardita Puspitadewi; Rini Sekartini (Indonesian Pediatric Society Publishing House, 2013)
Background Childhood obesity is a global health problem, with the prevalence is differed in each country and affected by many factors, such as lifestyle and physical activity. Insulin resistance (IR) as a basic mechanism of several metabolic diseases in obesity, is related with metabolic syndrome (MetS) along with its long term complications, such as type 2 diabetes mellitus (T2DM). Several factors are known to be associated with IR, and the presence of acanthosis nigricans (AN) has an important meaning in predicting IR. Objectives To assess the prevalence of IR, MetS in obese adolescents and its potentially associated factors, such as gender, signs of AN, and family history of metabolic diseases. Methods A cross-sectional study was performed in obese adolescents, aged 12-15 years, over a two-month period. Fasting blood glucose, insulin, and lipid profiles were measured. Obesity was defined using body mass index (BMI). Insulin resistance was quantified by the homeostasis model assessment for IR (HOMA-IR) . Metabolic syndrome was defined according to the International Diabetes Federation (IDF) 2007 criteria. Results Of92 obese adolescents, IR was found in 38% of subjects, with females predominating (57.2%). Signs of AN were seen in 71. 4% of subj ects and a positive family history of metabolic diseases was found in 82.8% of subjects, including family history of obesity, type 2 diabetes mellitus (T2DM), and hypertension. Less than 10% of subjects were considered to be in a prediabetic state, and none had T2DM. No statistical significance was found between gender, family history, or signs of AN and IR (P>0.05). Metabolic syndromes was found in 19.6% of subjects, with the fo llowing prevalences for each component: 34.8% for hypertension, 78.3% for central obesity, 8.7% for impaired fasting glucose (IFG), 22.8% for low levels of HDL, and 2 1. 7% for high triglyceride levels. A strong correlation was found between IR and IFG with OR= 5 .69 (95%CI 1.079 ~ 29.993, P= D.04). Conclusion We find a high prevalence ofIRin obese adolescents, and IR increases the risk of prediabetes. Thus, prevention strategies are needed to overcome the long term impact of obesity on health.